The Dobsonfly Genus Nevromus Rambur, 1842 (Megaloptera: Corydalidae: Corydalinae) from Thailand, with Description of a New Species - Piraonapicha , Kanyakorn; Jaitrong, Weeyawat; Liu, Xingyue; Sangpradub, Narumon (Tropical Natural History, 2021)
Nevromus Rambur, 1842 is a megalopteran genus belonging to the family Corydalidae, and endemic to the Oriental faunal region. The Thai species of Nevromus are herein revised to include two species: Nevromus aspoeck Liu, Hayashi & Yang, 2012, and Nevromus jeenthongi sp. nov. The larval and pupal stages of N. aspoeck are described here for the first time. Nevromus jeenthongi sp. nov. appears to be closely related to N. aspoeck but differs from the latter species the occiput without black spots, the broader posterolateral lobes of male ninth sternum, and the fused male tenth gonocoxite strongly concaved along dorsal outline. Both species inhabit clean, clear flowing streams. The geographical distribution of Nevromus is updated with first records of this genus from the Malay Peninsula and Myanmar. A key to species of the genus based on male is provided.